2007
DOI: 10.1021/es0629716
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Relationships among PCDDs/Fs, PCNs, PAHs, ClPhs, and ClBzs in Municipal Waste Incineration

Abstract: An extensive investigation was conducted to understand polychlorinated dibenzo-p-dioxin and furan (PCDD/F) formation mechanisms and their relationship with other organic compounds. PCDD/F, chlorophenols (CIPhs), chlorobenzenes (CIBzs), polyaromatic hydrocarbons (PAHs), and polychlorinated naphthalenes (PCNs) were analyzed in the boiler exit gases of a field-scale municipal solid waste incinerator under various operating conditions. The TEQ value and the concentration of target compounds changed with incinerato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 27 publications
11
65
2
Order By: Relevance
“…To our knowledge, emissions of PCNs from medical waste incinerators, hazardous waste incinerators, and cement kilns with hazardous waste disposal have, however, not been reported. The concentrations of PCNs emitted from waste incinerators in this study were higher than those of five MSW incinerators reported by Abad et al (1999), but lower than that of raw gas from a MSW incinerator reported by Oh et al (2007). The dioxin-like toxicity of PCNs has been investigated in previous studies (Hanberg et al 1990;Blankenship et al 2000;Villeneuve et al 2000).…”
Section: Concentration Of Pcns Emitted From Waste Incinerators Investcontrasting
confidence: 46%
See 3 more Smart Citations
“…To our knowledge, emissions of PCNs from medical waste incinerators, hazardous waste incinerators, and cement kilns with hazardous waste disposal have, however, not been reported. The concentrations of PCNs emitted from waste incinerators in this study were higher than those of five MSW incinerators reported by Abad et al (1999), but lower than that of raw gas from a MSW incinerator reported by Oh et al (2007). The dioxin-like toxicity of PCNs has been investigated in previous studies (Hanberg et al 1990;Blankenship et al 2000;Villeneuve et al 2000).…”
Section: Concentration Of Pcns Emitted From Waste Incinerators Investcontrasting
confidence: 46%
“…These compounds may be co-formed by similar mechanisms or may serve as reactants to form PCNs. Oh et al (2007) found that a strong correlation existed between PCNs and PCDFs and adjacent PCN homologue groups were closely related to one another. They suggested that PCN formation was related to chlorination/dechlorination mechanisms, similar to PCDFs formation.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the total PCN concentrations were much higher than the total 2378-PCDD/Fs concentrations, the PCN TEQs were lower than the PCDD/Fs TEQs due to the lower RPFs of PCNs. The PCN concentrations emitted from flue gas during the thermal wire reclamation process were higher than from other industrial sources, including municipal waste incineration (MWI), the coking industry, and secondary copper and lead smelting [28][29][30]. This indicates that thermal wire reclamation might be an important PCN emission source in the scrap metal dismantling industry.…”
Section: Concentrations Of Unintentional Pops Emitted From Thermal Wimentioning
confidence: 97%